An aromatic substance, eugenol induces distinct depressant effects on respiratory activity in different postnatal developmental stages of the rat. (June 2020) - Kotani, Sayumi; Yazawa, Itaru; Onimaru, Hiroshi; Izumizaki, Masahiko
Highlights: An aromatic substance, eugenol exerts analgesic and neuroprotective effects. We examined the effects of eugenol on respiratory activity in in vitro and in situ preparations. Eugenol shortened inspiratory burst duration in the newborn rat in vitro preparation. Eugenol decreased inspiratory burst amplitude in the juvenile rat in situ preparation. These differences might reflect developmental changes of the respiratory centers in each preparation. Abstract: Eugenol modulates neuronal activity through actions on voltage-gated ionic channels and/or transient receptor potential channels. We previously suggested that eugenol inhibited cellular (and/or network) mechanisms essential for the maintenance of the respiratory burst activity in a brainstem-spinal cord preparation from newborn rat (postnatal day 0–3). Study of the distinct effects of eugenol in neonatal and later developmental stage rats may offer new information about postnatal developmental changes of respiratory neuron networks. In the present study, therefore, we compared effects of eugenol in an in vitro newborn rat preparation with those in an arterially perfused in situ preparation from juvenile rat (postnatal day 12–15). In the former preparation, application of 1 mM eugenol decreased respiratory rate and inspiratory burst duration. In contrast, in the latter preparation, 1 mM eugenol induced a gradual decrease in the amplitude of integrated phrenic nerve activity. Phrenic nerve activity gradually recovered at 25–30 min after washout with a burst duration similar to control values. We hypothesized that the depressant effects of eugenol were caused by inhibition of cell excitability in the neonatal rat in vitro preparation but by a reduction of synaptic interactions in the juvenile rat in situ preparation.